Bat activity at a major road in Sweden - Sjölund, Amanda (SLU/Dept. of Ecology, 2015)
Humans have changed ecosystems steadily over the years, leading to habitat fragmentation and loss. Road- and railroad networks are rapidly expanding around the world and disintegrating natural landscapes. Habitat loss, habitat fragmentation and habitat degradation are three factors why bat species are threatened, and infrastructure such as roads has the potential to contribute to all of these factors. This is the first study of bats and the impact roads have on bats in Sweden. In this study we tested whether the major road acts as a barrier to movement of four different taxa of bats. Especially we focused on the activity of Myotis species at various environments in the landscape in relation to a major road. We placed auto boxes that automatically record bat ultra sounds in 34 study sites around Enköping for seven weeks. We had 8 sites along a major road, 8 sites in open gaps between forests without any roads, 4 sites at wildlife passages and 14 control sites within the forest. The results of this study show avoidance behaviour in Myotis, and Eptesicus species. For Nyctalus` the road does not reveal to be any obstacle. Observations of Pipistrellus species were too few to draw any conclusions. An important conclusion in this study is that there is not a difference in Myotis- activity between the road and open gaps in the forest. Both types of openings are avoided. However, wildlife passages are used for foraging and commuting. It is important to do further studies to improve the mitigation measures for bats in infrastructure projects in Sweden. More knowledge about the different taxa’s behaviour near major roads and an understanding of the thresholds, such as limit distances for Myotis in open gaps are necessary to draw conclusions about mitigation measures and alternatives for ecoducts.